Designing an Accounting Information System for Financial Position Reports in A Garment Business Using PHP And MySQL - Nuraini, Rizki; Supriyati (Universitas Komputer Indonesia, 2025)
A garment business still manages its financial transactions and reporting manually, which often results in difficulties related to accuracy, data inconsistency, and delays in report generation. This research aims to design an accounting information system using PHP and MySQL to support structured, efficient, and accurate financial reporting. The method used in this study is the waterfall development model, which includes stages of analysis, design, implementation, and testing. The resulting system is web-based and allows users to record transactions, manage inventory and vendor data, post to journals and ledgers, generate trial balances, and produce financial position reports in accordance with SAK EMKM. The system also provides a cost of goods sold (COGS) calculation feature. Based on implementation and evaluation, the system significantly improves the efficiency and accuracy of financial data processing at Khomsah Kholifah and helps the business owner in decision-making by providing structured, real-time financial information